Exploring the relationship between teachers' social intelligence and classroom discipline strategies - Jeloudar, Soleiman Yahyazadeh; Md. Yunus, Aida Suraya (Canadian Center of Science and Education, 2011)
The purpose of the study is to analyze the social intelligence level of teachers employed in government secondary schools in Malaysia based on selected demographic variables such as age, and how they relate to the classroom discipline strategies used. The sample of the study comprises 203 teachers. The study also revealed that there were significant differences between teachers’ age groups and their social intelligence. Further a significant relationship was noted between teachers’ social intelligence and the six strategies of classroom discipline strategies (discussion, recognition, involvement, hinting, punishment and aggression).